Harmonizing European Financial Regulation: Is There a Need for Improved Similarity in Prospectus Liability Rules? - Sandtorv, Leif (Review of European and Comparative Law, 2024)
This paper on financial regulation addresses the extent to which rules on liability for information should be standardized across the EU/EEA region. The method applied is an analysis of legal documents. My finding is that further harmonization may lead to difficulties concerning procedural rules. Some authors suggest harmonizing the civil procedure for prospectus liability cases. This could reduce asymmetric information and thus contribute to efficient markets. However, mandatory disclosure comes with costs. These may increase if standards inconsistent with domestic procedures are imposed. The topic may be of interest for regulating other aspects of life, such as environmental information disclosure.